CONSTANT RATE OF SUPPLY (CRS) MODEL FOR DETERMINING THE SEDIMENT ACCUMULATION RATES IN THE COASTAL AREA USING 210Pb - Ali Arman Lubis (JOURNAL OF COASTAL DEVELOPMENT, 2006)
A CRS model has been applied to determine the ages and accumulation rates of sediment. This model assumes a constant flux of unsupported 210Pb to the sediment, allows the rate of sedimentation to vary over time. The applicable of CRS model was used to analysis of two bottom sediment cores (JB 17 and JB 11) from Jakarta Bay. The result show that sediment accumulation rates in JB 17 varied from 0.09 to 1.13 kg.m-2.y-1 and in JB 11 varied from 0.18 to 2.47 kg.m-2.y-1.